1997
DOI: 10.1017/s0022215100138137
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal tuberculosis at the end of the 20th century

Abstract: Despite the dramatic reduction in the incidence of laryngeal tuberculosis after the 1950s, the topic has now gained new interest due to claims that the disease has changed its clinical pattern. In the past, the typical patient was 20-40 years old with ulcerated laryngeal lesions, perichondritis, and advanced cavitary lung disease. We studied nine cases of laryngeal tuberculosis confirmed by histological examination. The microlaryngoscopy revealed tumour-like lesions and/or chronic non-specific laryngitis. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
4
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 10 publications
8
42
4
2
Order By: Relevance
“…A study by Auerbach found that 698 (92.3%) of 700 autopsied cases of laryngeal tuberculosis had advanced pulmonary tuberculosis [1]. While it has been reported that primary laryngeal tuberculosis has been increasing in recent years [8,13,20], the majority of cases show positive findings on X-rays in not only our study but also in others [14,19,21]. Those studies support that bronchogenic route is the main cause of infection.…”
Section: Image Diagnosis and Sputum Examinationsupporting
confidence: 81%
“…A study by Auerbach found that 698 (92.3%) of 700 autopsied cases of laryngeal tuberculosis had advanced pulmonary tuberculosis [1]. While it has been reported that primary laryngeal tuberculosis has been increasing in recent years [8,13,20], the majority of cases show positive findings on X-rays in not only our study but also in others [14,19,21]. Those studies support that bronchogenic route is the main cause of infection.…”
Section: Image Diagnosis and Sputum Examinationsupporting
confidence: 81%
“…Severe ulcerative or granulomatous lesions in the posterior larynx were the most prevalent types in the past, however, it has been reported that more cases of laryngeal tuberculosis affect whole larynx but few with regional infection in the posterior larynx [8][9][10]. Furthermore, it has been reported that hypertrophic, exophytic, polypoid lesions or non-specific lesions are seen relatively more frequently than ulcerative or granulomatous lesions as in our case [4,5,8,11]. Henceforth it is imperative for the physicians to perform stroboscopic examination and test chest radiograph, sputum study, and laryngeal biopsy when nonspecific infection occurs unilaterally for definitive diagnosis of laryngeal tuberculosis and to differentiate from chronic laryngitis.…”
Section: Discussioncontrasting
confidence: 43%
“…Earlier, it affected posterior larynx in most patients, since it directly spreads along the airway [1][2][3][4][5][6]. Currently, however, it is prevalent in all parts of the larynx and is usually seen in people in their 40s-60s as primary laryngeal tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 In the present two cases, both the lesions were restricted to unilateral vocal cord superior surface without involving any other area of the larynx. However, in both the cases, the supraglottic laryngeal mucosa showed marked congestion, which is similar to that observed by Singh et al 9 In a study of tubercular laryngitis in 14 patients, Ozüdogru et al 12 had observed that glottal closure presented an irregular shape during treatment, and later became spindle shaped along its entire length.…”
Section: Ijoplmentioning
confidence: 48%